Anatomy of Injury Severity and Fatality in Indonesian Traffic Accidents - Santosa, Sigit Puji; Mahyuddin, Andi Isra; Sunoto, Febrianto Guntur (ITB Journal Publisher, LPPM ITB, 2017)
There has been a steady increase in traffic accidents with major injuries in Indonesia over the last 10 years, especially those with a score higher than 3 on the Abbreviated Injury Scale (AIS). Frontal, side, and rear collisions, as well as pedestrian impact are modes of accident that contribute to the majority of injuries or fatalities. Based on age classification, the 16-30 age group are the most vulnerable road users in Indonesia. Traffic accidents in Indonesia are dominated by motorcycles, which also contribute the highest portion of fatalities and major injuries (AIS score > 3). Most traffic accidents can be attributed to human, road and environmental, or vehicle factors. Careless driving and unruly behavior of the driver are the main causes of accidents in Indonesia. Statistical data and analyses on traffic accidents in Indonesia can be used to develop a comprehensive strategy and policy to reduce the number of fatalities and severe injuries of road accidents in Indonesia. There is a need to balance the high growth of motor vehicles with adequate infrastructure. Good driver education as well as vehicle safety and crashworthiness regulations are required in order to reduce traffic accident fatalities.